FUNCTIONAL TESTING OF THE VARIABLE GEOMETRY SUSPENSION (VGS) PROTOTYPE ON BUMPY ROAD CONDITIONS - Murti, Dafa Aditya; Huda, Miftachul; Abdi, Ferly Isnomo; Wulandari, Diah; Firman Yasa Utama (SYNTIFIC, 2024)
Background. Modern vehicles must prioritize comfort and safety, including the suspension system. While passive suspension systems are common, they struggle with excessive vibrations on uneven roads. Semi-active and active systems address this but are costly and complex. To solve this, a Variable Geometry Suspension (VGS) prototype was developed, integrating an active actuator into a passive system to adjust its geometry, providing performance comparable to active suspension systems. Research Purpose. This study aims to examine the effect of single-link angle variations in the Variable Geometry Suspension (VGS) prototype on bumpy roads to determine the most comfortable single-link angle. Research methods. This research employs a Research and Development (RnD) method by testing the single-link angle at 0°, 90° (reference angle), and 180°. Data collection was conducted by introducing road disturbances in the form of a bumpy road. Findings. The testing results showed that the lowest Root Mean Square (RMS) value of the sprung-mass was at a single-link angle of 90°, with an RMS value of 0.72 m/s². This indicates a